2013
DOI: 10.1111/pbi.12098
|View full text |Cite
|
Sign up to set email alerts
|

Tomato cystatin SlCYS8 as a stabilizing fusion partner for human serpin expression in plants

Abstract: Keywords: alpha-1-antichymotrypsin, fusion proteins, peptide linkers, plant cystatins, plant-based protein expression, recombinant proteins. SummaryStudies have reported the usefulness of fusion proteins to bolster recombinant protein yields in plants. Here, we assess the potential of tomato SlCYS8, a Cys protease inhibitor of the cystatin protein superfamily, as a stabilizing fusion partner for human alpha-1-antichymotrypsin (a1ACT) targeted to the plant cell secretory pathway. Using the model expression plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 74 publications
4
57
1
Order By: Relevance
“…benthamiana leaves. They also suggested a negative impact of protease inhibitor co-expression on IgG accumulation as observed with other proteins [30,36], strongly compensated by the heavy chain-stabilizing effect of co-secreted Sl CYS8 in upper and middle leaves.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…benthamiana leaves. They also suggested a negative impact of protease inhibitor co-expression on IgG accumulation as observed with other proteins [30,36], strongly compensated by the heavy chain-stabilizing effect of co-secreted Sl CYS8 in upper and middle leaves.…”
Section: Resultsmentioning
confidence: 89%
“…Studies have also discussed the potential of protease inhibitors as co-expression partners to enhance the stability of clinically-useful recombinant proteins, including mammalian IgGs [13, 2932, 36, 47, 48]. In line with these studies and with studies reporting the negative impact of host plant Cys proteases on the integrity of several recombinant proteins in plants [13, 26, 28, 31, 49], we here observed a significant stabilizing effect of tomato Sl CYS8 on the H10 antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glycosylation process is initiated during protein translocation into the ER and the addition of N -glycans to the protein has been linked to diverse roles, including stability against denaturation and proteolysis, fine-tuning the charge and isoelectric point, regulating protein turnover [30], and has also been linked to protein activity [31]. Although some glycoproteins may accumulate well in the cytosol [32] and chloroplasts [33], and perform the required biological functions, others such as An PGI may require glycosylation for stability and will not accumulate in those compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization of linkers has been shown to improve both protein expression yield and biological activity [40]. A recent study comparing several linkers demonstrated the need for empirical evaluation of different linkers, and the possible beneficial effect of twistable linkers on activity of the fusion partners, possibly by allowing a reorientation of the functional domains [32]. Moreover, the addition of ELP and HFBI fusions had adverse effects on enzyme activity.…”
Section: Discussionmentioning
confidence: 99%